2016
DOI: 10.1055/s-0036-1597327
|View full text |Cite
|
Sign up to set email alerts
|

Does Circadian Variation of Mothers Affect Macronutrients of Breast Milk?

Abstract: To determine the within-day variation of fat, protein, and carbohydrate content of breast milk. The study was conducted at Zekai Tahir Burak Maternity Teaching Hospital between April 2013 and January 2014. We obtained milk samples from lactating mothers of hospitalized infants through hand expression after breast-feeding or pumping three times a day. A mid-infrared human milk analyzer was used for measuring the macronutrient contents of breast milk samples. Lactating mothers of 52 infants (30 preterm, 22 term)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Carbohydrates serve as an important energy source for neonatal metabolism, especially for the brain [ 22 ]. As shown in three independent studies of sufficient quality [ 23 , 24 , 25 ], total carbohydrate concentration in human milk does not show any circadian variation. For glucose, more research is necessary since the only two studies [ 26 , 27 ] on this component are contradictive.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Carbohydrates serve as an important energy source for neonatal metabolism, especially for the brain [ 22 ]. As shown in three independent studies of sufficient quality [ 23 , 24 , 25 ], total carbohydrate concentration in human milk does not show any circadian variation. For glucose, more research is necessary since the only two studies [ 26 , 27 ] on this component are contradictive.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, they are an important source of energy [ 31 ]. The total protein content of human milk does not exhibit circadian variation in nine out of eleven studies [ 23 , 24 , 25 , 28 , 29 , 32 , 33 , 34 , 35 ]. In the two studies [ 27 , 36 ] that do indicate a circadian rhythm in total protein concentration, the acrophase (peak) is discordant and, therefore, it potentially indicates false-positive findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is yet no clear explanation but only suggestions and speculations of why these diurnal fluctuations of human milk composition exist and what impact they have on a newborn's health and development. Hormonal changes in lactating women, breastfeeding patterns, the influence of the degree of breast fullness, circadian dietary habits, ethnic differences, and different techniques for the measurement of milk macronutrients are among the factors that can influence circadian changes in milk composition [9,27,29,30]. However, the particular role of each factor and why and how these factors affect dynamic changes in specific macronutrients are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in analytical technologies enabling the growth of data over the past decade, HM composition remains only partially elucidated [1,2,3,4]. Recent studies revealed countless inter- and intra-individual factors influencing HM composition, such as maternal, circadian, pregnancy, delivery, infantile, chronological and environmental variables [5,6,7,8,9]. Among these factors, temporal changes of HM composition before and after term equivalent time are of particular interest considering the critical challenges of preterm (PT) infants’ nutrition and the critical importance of HM for this vulnerable population [10,11].…”
Section: Introductionmentioning
confidence: 99%